(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
Finding a first job, the discrepancy between the level and quality of education professional duties, lack of experience – all the problems faced by young people in finding a job. According to the UN, the world every third employable not work at all or have casual or seasonal income. Unemployment is a central social problem of modern society. Unemployment may not be feasible or economically or socially, as its growth creates a range of problems: reduced purchasing power, the budget loses taxpayers, the company – staff.